An institutional approach to cross-national distance - Berry, Heather; Guillén, Mauro F; Zhou, Nan (Journal of International Business Studies, 2010)
Cross-national distance is a key concept in the field of management. Previous research has conceptualized and measured cross-national differences mostly in terms of dyadic cultural distance, and has used the Euclidean approach to measuring it. In contrast, our goal is to disaggregate the construct of distance by proposing a set of multidimensional measures, including economic, financial, political, administrative, cultural, demographic, knowledge, and global connectedness as well as geographic distance. We ground our analysis and choice of empirical dimensions on institutional theories of national business, governance, and innovation systems. In order to overcome the methodological limitations of the Euclidean approach, we calculate dyadic distances using the Mahalanobis method, which is scale-invariant and takes into consideration the variance–covariance matrix. We empirically analyze four different foreign expansion choices of US companies to illustrate the importance of disaggregating the distance construct and the usefulness of our distance calculations, which we make freely available to managers and scholars.